La deserción escolar y las familias extensas. - Quishpe Chicaiza, María Pilar (2018)
Attrition refers to the abandonment of studies by the child and is one of the problems faced by the General Basic Education, since the fact that children interrupt their educational training is worrisome, as this impacts in their lives in the present and future. Thus, school dropout is influenced by several factors including family, economic, health, affective and pedagogical, which increase the student risk towards dropping out of school. In our work, each of these factors will be analyzed and each one of these will be developed in a descriptive way, reflecting on this problem.We have taken as reference the main cause and problem of school dropout, families are extensive because if a family has more than five children, they are unable to provide a quality education to each of them, so to verify this fact research has been used as a methodology, which was applied in the Manuela Sáenz Educational Unit, especially in the seventh year students, where the highest rate of deserters was clearly evident, since many want to help with economic expenses at home, leaving aside their studies, after having conducted surveys of parents of teachers and students of the aforementioned institution, it can be concluded that, the economy is added among the influential factors in school dropout, many children stop studying due to lack of economic resources to join the world of work, In conclusion, school dropout is a problem that threatens education, the student, society and the development of the country. However, this problem can be counteracted if the factors that are involved are taken into account.It was possible to encourage all the beneficiaries of this project to understand the importance of finishing a school loss